2015
DOI: 10.4103/0019-5049.154998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of positive airway pressure during pre-oxygenation and induction of anaesthesia upon safe duration of apnoea

Abstract: Background and Aims:Induction of general anaesthesia per se as also the use of 100% oxygen during induction of anaesthesia, results in the development of atelectasis in dependent lung regions within minutes of anaesthetic induction. We aimed to assess the effect of application of a continuous positive airway pressure (CPAP) of 5 cm H2O during pre-oxygenation and induction of anaesthesia on the period of apnoea before the occurrence of clinically significant desaturation.Methods:In this prospective, randomised,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 15 publications
1
27
0
1
Order By: Relevance
“…This may be the first study evaluating the role of CPAP in paediatric patients during anaesthesia induction. However, despite the shortage of investigations in children, there have been many studies that have evaluated the application of positive airway pressure in adult populations during preoxygenation and anaesthesia induction [20][21][22][23][24]. Their results point mostly in the same direction as ours, showing improvements in outcomes, such as longer duration of apnoea before clinically significant arterial desaturation, better oxygenation and prevention of desaturation episodes, upon the use of positive airway pressure.…”
Section: Plos Onementioning
confidence: 66%
See 1 more Smart Citation
“…This may be the first study evaluating the role of CPAP in paediatric patients during anaesthesia induction. However, despite the shortage of investigations in children, there have been many studies that have evaluated the application of positive airway pressure in adult populations during preoxygenation and anaesthesia induction [20][21][22][23][24]. Their results point mostly in the same direction as ours, showing improvements in outcomes, such as longer duration of apnoea before clinically significant arterial desaturation, better oxygenation and prevention of desaturation episodes, upon the use of positive airway pressure.…”
Section: Plos Onementioning
confidence: 66%
“…In paediatrics, the application of CPAP has been widely studied in patients with bronchiolitis as an alternative to controlled mechanical ventilation [18,19]. Although the evidence for its use during anaesthesia induction in children is limited, the results obtained in the adult population are encouraging [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to correlation with gender the same study [1] found that females had a tendency towards shorter duration of non-hypoxic apnoea as compared with males in the PEEP group, but this difference was not observed in the ZEEP group. The application of CPAP or PEEP can have potentially deleterious effects on the cardiovascular system, however a study done by Cressy DM et al [18][19], using a CPAP of 7.5 cm H2O did not find any adverse effects on systolic and diastolic blood pressure . As we have used a CPAP of 5 cm H2O during pre-oxygenation, it is unlikely to have produced any significant effects on the heart rate and blood pressure.…”
Section: Discussionmentioning
confidence: 94%
“…A recent study done by Edmark L et al, has shown that oxygen concentrations as high as 80% are sufficient to diminish atelectasis formation compared to 100% oxygen, however the time of non-hypoxic apnoea is decreased by more than 90 seconds. [18][19] A previous study by Rusca M et al [20] have shown that the application of positive end expiratory pressure throughout the induction of anaesthesia effectively prevents atelectasis formation despite the use of 100% oxygen. In a study conducted by Herriger A et al [1] Patients who received continuous positive airway pressure during preoxygenation and anaesthesia induction had higher arterial oxygen tensions and tolerated significantly longer duration of apnoea as compared to the patients who did not received such manoeuvers, but the authors could not distinguish between the effect of continuous positive airway pressure (CPAP) applied during preoxygenation and positive end expiratory pressure (PEEP) applied during mechanical ventilation before tracheal intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation